Emerging of the Idea of Criminalization of Corporate Misconduct in the Russian Federation - Anna V. SHASHKOVA; Ekaterina Kudryashova (Communications of International Proceedings, 2020)
The present article is dedicated to the problem of interaction between the state and corporations at the industrial period of society, establishment of corporations and their liability. The present article analyses positive and negative examples of participation of corporations in social problems' solution. The author researches corporate crimes and analyses those who have particular importance nowadays. The article focuses on different theoretical approaches towards ideas of establishing corporate criminal liability in the national legislation of the Russian Federation.  The article analyses such symbolic court precedents as those elaborated in the UK in cases ‘Santa Clara County v. Southern Pacific Railroad Co.’ in the USA and ‘Salomon v. Salomon & Co. Ltd’. The article states that at the stage of industrial society emerged the current concept of the corporation as a separate subject of the civil turnover with the necessary scope of rights and liabilities. The methodological ground of the present Article represents the dialectic scientific method of the socio-political, legal and organizational processes with the principles of development, integrity, consistency, etc. The consistency analysis method is used while researching the object of the analysis. Some public-private research methods are also used: formally-logical or comparative legal method are used to compare legislation of the United States of America, the United Kingdom and the Russian Federation in the area of corporate liability for bribery. The aim of the present article is to find the root of the problem of interaction between the state and corporations, to show political will behind introduction criminalization of corporate liability. The core part of the research is dedicated to the analysis of emerging of the corporate liability. The question on emerging of corporate liability is analysed from a political point of view concluding that at present the Russian Federation political conditions are not set in for the matter.
Keywords: Industrial Society; Corporate Liability; Criminal Liability; Corporate Crime.